Tension Pneumocephalus in Head Injury - Nayak, P. K. (Indian Journal of Neurotrauma, 2015)
Occurrence of pneumocephalus following a head trauma is relatively rare. Tension pneumocephalus can manifest as severe headache, dizziness, mental changes, and even seizure; therefore, urgent diagnosis and treatment are mandatory. The Mount Fuji sign on CT scans of the brain is useful in discriminating tension pneumocephalus from nontension pneumocephalus. Deterioration due to an increase in subdural air volume can be evacuated by craniotomy. Though uncommon, tension pneumocephalus is a life-threatening complication that requires urgent diagnosis and treatment.
Keywords: head injury; tension pneumocephalus; Mount Fuji sign